Elaboração de doce de leite light contendo probióticos microencapsulados - Simeoni, Caroline Posser (2015)
The dulce de leche is a typical product from Latin America, mainly in Brazil, Argentina and Uruguay. It‟s a product very appreciated by consumers because of its sensorial characteristics despite its high energy values. With the growing concern of the costumers in having healthy and low calories products which brings benefits to their health, this project aimed to develop a low fat dulce de leche adding microencapsulated Enterococcus faecium probiotics. The microcapsules were elaborated through the external ionic gelling by extrusion and they‟ve received a protein recover of whey milk protein concentrate (WPC) of 0,5% and 2%. In the control Treatment were added free culture of E. faecium. The thermical resistence, gastrointestinal resistance in vitro, protein rate water activity and morphology were analyzed. The dulce de leche was prepared with skim milk with 0.5% fat , replacing 20% of sacorose by sucralose, adding 3% inulin and probiotic microcapsules whit differents overcoat WPC concentrations. The dulce de leche was monitored during 90 days stored at 4 ºC. During this period it were analysed the viability of the probiotic, the microbiology of the product and the color and texure patterns while in the shelf. The microcapsules have the ideal shape and size to be added in the food and at the same time grant protection to the probiotic. The value of the capsules were significantly different among the treatments, ranging from 0,49% to 7,16% of protein adsorbed in the microcapsule. The microcapsules also granted thermal protection to the probiotic cells in the in vitro tests. The microencapsulated microorganisms presented countings of 8,21 and 9,28 Log UFC.mL-1to the treatments with an overlay of 0,5% and 2% of WPC respectively, while the free cells presented a viability of only 0,10 Log UFC.mL-1 after a heating of 70 ºC during 30 min. Therefore, about the viability of the probiotic strain, we can conclude that the microencapsulation influenced significantly the surviving of the probiotic, once the bacteria which have received the microcapsule had a viability at the end of its life in shelf above 7 Log UFC.g-1of the product, while the probiotics which haven‟t received the microcapsule haven‟t had the viability of the product at the end of its period of storage. However, the percentage of protein added to the microcapsule hasn‟t interfered in the survival of the bacterial strain. The results of the microbiological analysis have shown a significant reduction of positive S. aureus coagulase, moulds and yeasts during the storage of the product. The results found show that the substitution of the sucrose by sucralose and the fat by inulin reduced the caloric value of the dulce de leche. The texture results for hardness parameters, adhesiveness, gumminess and flexibility differed among the treatments during its life in shelf. In the analysis of the dulce de leche color we could notice a significant variant in the lightness parameter between the treatment without the microcapsules and the treatments that they were added. With these results we can conclude that it‟s possible to formulate low fat dulce de leche with probiotics throught the substitution of the sucrose and fat and using a microencapsulation to grant consistence and viability to the probiotic cells until the end of the product‟s life in shelf.